Heart failure patients' perceptions and use of technology to manage disease symptoms. - Hall, Amanda K.; Dodd, Virginia; Harris, Amy; Mcarthur, K.; Dacso, Clifford; Colton, LM (Telemedicine journal and e-health : the official journal of the American Telemedicine Association, 2014)
Technology use for symptom management is beneficial for both patients and physicians. Widespread acceptance of technology use in healthcare fuels continued development of technology with ever-increasing sophistication. Although acceptance of technology use in healthcare by medical professionals is evident, less is known about the perceptions, preferences, and use of technology by heart failure (HF) patients. This study explores patients' perceptions and current use of technology for managing HF symptoms (MHFS). A qualitative analysis of in-depth individual interviews using a constant comparative approach for emerging themes was conducted. Fifteen participants (mean age, 64.43 years) with HF were recruited from hospitals, cardiology clinics, and community groups. All study participants reported use of a home monitoring device, such as an ambulatory blood pressure device or bathroom scale. The majority of participants reported not accessing online resources for additional MHFS information. However, several participants stated their belief that technology would be useful for MHFS. Participants reported increased access to care, earlier indication of a worsening condition, increased knowledge, and greater convenience as potential benefits of technology use while managing HF symptoms. For most participants financial cost, access issues, satisfaction with current self-care routine, mistrust of technology, and reliance on routine management by their current healthcare provider precluded their use of technology for MHFS. Knowledge about HF patients' perceptions of technology use for self-care and better understanding of issues associated with technology access can aid in the development of effective health behavior interventions for individuals who are MHFS and may result in increased compliance, better outcomes, and lower healthcare costs.